Modern Models of Quality Management in Forensic Activities - S. A. Kuz’min (Теория и практика судебной экспертизы)
The article contains analysis of modern approaches to quality management in the forensic science institutions, reviewed evolution of the view about quality as an object of management. Author considered a structure and a volume of notion of forensic science activity and mark out the elements of structure that form complex factor that affects the quality. Based on international and one’s country experience is given the historical retrospective of process of development and deployment of mechanisms of managements of quality in production and forensic science. The conceptual approaches to quality problems enshrined in the series ISO 9000 and ISO/IEC 17025 international standards, their similarities and distinction, and also applicability limits concerning activity of the forensic science institutions are analyzed. The special attention is paid to the analysis of problems arising in the design and implementation of quality management systems, identified their causes, and made recommendations for improving the effectiveness of management.